Significados construidos alrededor del desgaste emocional en pareja relacionado con la malformación congénita (2022)
According to studies conducted by the ICBF Colombian Institute of Family Welfare, it is evident that the supposed prioritization of social programs and the construction of lines of action to guide and strengthen couples who have a child with a structural congenital malformation during the process of custody and upbringing, has not resulted in benefits for this population, therefore, the emotional toll is more evident.